(untitled) (Research, Society and Development, 2020)
This work aims to analyze the behavior of the graph of a quadratic function, with the variation of its coefficients, interpreting the relationships established between its algebraic and graphical representations, using the geogebra software environment for this. The methodological procedure included the exploration and investigation of quadratic functions using the tools of the geogebra software, for the analysis of the behavior of the graph of this function due to variations in the values of its coefficients. In the analyzes we studied the remarkable points of the quadratic function, making the identification of its roots and the vertex of the parabola. We also proceed with the analysis of the variation of each function coefficient individually, ending with the analysis of the variation of the quadratic function discriminant. We conclude that, with the proper use of the tools of the geogebra software, and thanks to its dynamic aspect, it is possible to identify and interpret more efficiently the existing relationships between the algebraic and graphical representations of this function.